2004
DOI: 10.1093/nar/gki069
|View full text |Cite
|
Sign up to set email alerts
|

CDD: a Conserved Domain Database for protein classification

Abstract: The Conserved Domain Database (CDD) is the protein classification component of NCBI's Entrez query and retrieval system. CDD is linked to other Entrez databases such as Proteins, Taxonomy and PubMed®, and can be accessed at http://www.ncbi.nlm.nih.gov/entrez/query.fcgi?db=cdd. CD-Search, which is available at http://www.ncbi.nlm.nih.gov/Structure/cdd/wrpsb.cgi, is a fast, interactive tool to identify conserved domains in new protein sequences. CD-Search results for protein sequences in Entrez are pre-computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
765
0
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,024 publications
(781 citation statements)
references
References 9 publications
5
765
0
5
Order By: Relevance
“…A single inner membrane translocase The Tim17-Tim22-Tim23 family of proteins (PFAM: PF02466) [22] are a set of highly-conserved proteins found in animals, plants, fungi and protists that range from Plasmodium to Trichomonas [2,23,24]. In all cases, the protein has four predicted transmembrane domains with specific amino acid signature motifs [23].…”
Section: The Protein Import Machinery In Trypanosoma Bruceimentioning
confidence: 99%
“…A single inner membrane translocase The Tim17-Tim22-Tim23 family of proteins (PFAM: PF02466) [22] are a set of highly-conserved proteins found in animals, plants, fungi and protists that range from Plasmodium to Trichomonas [2,23,24]. In all cases, the protein has four predicted transmembrane domains with specific amino acid signature motifs [23].…”
Section: The Protein Import Machinery In Trypanosoma Bruceimentioning
confidence: 99%
“…This is the only open reading frame in F. acidarmanus Fer1 predicted to be a functional DNA ligase so, for convenience, we refer to this gene as falig and its protein product as FaLig. Three regions of the predicted amino acid sequence have significant similarity to domains within the Conserved Domain Database (CDD) (Marchler-Bauer et al 2005) (Fig. 1a).…”
Section: Identification Of An Atp-dependent Dna Ligase Within the Genmentioning
confidence: 99%
“…Primary sequence analysis of At1g77540 revealed that it belongs to the biochemically uncharacterized COG2388 family, which shows sequence relationship to the GNAT family of histone acetyltransferases (HATs) (30). We investigated this relationship in more detail and established that At1g77540 is indeed capable of binding acetyl-CoA as well as acetylating histones H3 and H4.…”
Section: Discussionmentioning
confidence: 99%